Reflexivity on medicalisation of the mind and the biomedical invasion on being human - Mapaling, Curwyn; Naidu, Thirusha (PINS-Psychology in Society, 2023)
Clinical psychology practice is characterised by three core functions; assessment, diagnosis, and treatment. We challenge the biomedical imperative in clinical psychology through our shared personal experiences in training as clinical psychologists in South Africa. We pose that the training of clinical psychologists historically was and continues to be focused through a biomedical lens. Alluding to the perennial debate on the relevance of psychology and current arguments around the contemporary relevance of clinical psychologists’ training; we propose clinical-community psychology as the main way forward for psychology practice in South Africa. Our position is that in South Africa, clinical psychology training and services should be appropriate and equitable in response to the needs of individuals and communities. We highlight the lack of contextual relevance that has been perpetuated in most of the clinical psychology training programmes. This misplaced historical legacy does not serve the people within the South African context. Current and future clinical psychology training should be re-aligned toward the service of members of the South African communities and settings.